Lipid Recovery from Concentrated Emulsions by Freezing–Thawing as an Alternative to Solvent‐Based Extraction: A Case Study on Mayonnaise. Issue 11 (17th October 2022) - Okuro, Paula K.; Viau, Michèle; Kermarrec, Alice; Cunha, Rosiane L.; Meynier, Anne; Berton‐Carabin, Claire
Abstract: Most analyses concerning the characterization of lipids present in complex food systems require separation and recovery of lipids prior to analysis. This may be achieved, for example, by solvent‐based extractions. In the case of concentrated emulsions, targeted physical destabilization and phase separation induced by a freeze–thaw treatment are also considered. This strategy would imply a simple, solvent‐free method with a high yield. In the present work, conventional mayonnaise and a vegan alternative are evaluated. The effect of the freezing–thawing conditions on lipid recovery, as compared to a classical solvent (hexane:n‐2‐propanol, 3:2 v/v)‐based extraction is investigated. In particular, two freezing temperatures (−20 and −80 °C) and the presence or not of additional water to aid phase separation are evaluated. The freezing temperature (which directly influences the rate and extent of water and lipid crystallization) largely impacts lipid recovery, in a matrix‐dependent manner: −20 °C is clearly the most suitable temperature for the conventional mayonnaise, whereas −80 °C seems somewhat better for the vegan alternative. Importantly, this alternative freezing–thawing approach does not alter the fatty acid composition nor the lipid class profile compared to a classical solvent extraction, which confirms its relevancy from a subsequent analytical perspective. Practical Applications : The induction of emulsion destabilization by freezing–thawing is a simple, high‐yield and solvent‐free methodology (i.e., compatible with green chemistry) for lipid recovery regarding analytical purposes. Lipid recovery can be greatly improved by settling the involved conditions. Herein authors propose some guidelines for selecting and reasoning over procedure parameters in concentrated emulsions. The performance of lipid recovery is tuned by the conditions of freezing and guided by the type of emulsion. Abstract : Freezing‐thawing is a simple alternative to classical solvent extraction for recovering lipids from concentrated emulsions such as mayonnaise. High lipid amounts can be recovered by tuning the freezing temperature and water addition in a matrix‐oriented manner. The fatty acid composition and lipid class profile are comparable for freezing‐thawing and solvent extraction, which opens perspectives for using the freezing‐thawing method for eventual analytical purposes.